Discrete Ou-Iang type inequalities - Li, Wen-Rong; Cheng, Sui Sun (Tamkang Journal of Mathematics, 2000)
Discrete Ou-Iand type inequalities are established which find applications in stability of difference equations with sublinear perturbations.